2012
DOI: 10.1017/s1478951512000430
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life from the perspective of the palliative care patient in a resource-poor community in South Africa

Abstract: Life was a daily struggle for survival. Poverty was so overwhelming that quality of life was primarily measured in terms of the ability to buy food and other basic commodities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…Outcome evaluations of palliative care services could be designed based on a supportive care framework to ensure holistic evaluations (Fitch, 2008). Much of the focus on these palliative care services has been on pain management, with other aspects like quality of life neglected (Selman et al, 2011; Jansen van Rensburg et al, 2013). Therefore, using a supportive care framework to evaluate these services will provide better information on how palliative care domains are addressed and suggest areas for improvement.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Outcome evaluations of palliative care services could be designed based on a supportive care framework to ensure holistic evaluations (Fitch, 2008). Much of the focus on these palliative care services has been on pain management, with other aspects like quality of life neglected (Selman et al, 2011; Jansen van Rensburg et al, 2013). Therefore, using a supportive care framework to evaluate these services will provide better information on how palliative care domains are addressed and suggest areas for improvement.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…As applicable to our study, this design enabled us to investigate dimensions previously unexplored and make comparisons with data from other studies (Grove et al, 2013). The data used in the secondary analysis were originally gathered to describe QoL from the perspective of the palliative patients living in a resource-poor community in Tshwane (Jansen van Rensburg, 2011; 2013). This consisted of qualitative data gathered from 10 participants who were between the ages 30 and 79, and who had a variety of primary diagnosis (e.g., confirmed and suspected AIDS, cancer, cerebrovascular incidents, arthritis, and tuberculosis).…”
Section: Methodsmentioning
confidence: 99%
“…The research problem of our study speaks to the QoL domains identified by palliative patients living in a resource-restricted community in South Africa and the domains assessed by multidimensional QoL instruments used in African palliative care. Jansen van Rensburg (2011), in a qualitative study exploring QoL from the perspective of underprivileged palliative patients living in Tshwane, South Africa, found that various factors in addition to symptom control influence quality: poverty, employment and ability to work, social support, religion, receiving a government pension, isolation, rejection, and stigmatization. These findings support the finding of Selman et al (2011 b ) that the unique challenges faced by Africa influence the nature of QoL domains.…”
Section: Research Problem and Questionmentioning
confidence: 99%
“…Only the studies by Cohen et al 34 and Osborne et al 47 included all eight aspects. All but one study reported that spiritual, physical, and social aspects were important, whereas only a quarter 36 Goldsteen 2006 37 Gott 2008 38 Gourdji 2009 39 Greisinger 1997 40 Jansen van Rensburg 2013 41 Kim 2009 42 Locker 2015 43 Masson 2002 44 Melin Johansson 2006 45 Melin Johansson 2008 46 Osbourne 2014 47 Payne 1996 48 Pierson 2002 49 Rowland 2014 50 Sherman 2001 51 Steinhauser 2000 52 Stridsman 2015 53 Treloar 2009 54 Vig 2003 55 Willems 2004 56Shaded cells represent important aspects included in the study.…”
Section: Aspects Quality Of Life Important From Palliative Care Patiementioning
confidence: 99%